حماية_المدنيين_أثناء_النزاعات_المسلحة_الدولية - منال سليمان; نور الإسلام سليماني (My University, 2025)
Summary International armed conflicts represent one of the most pressing challenges facing the international community due to their complex legal, political, and humanitarian dimensions. International humanitarian law defines an international armed conflict as a confrontation between two or more states, regardless of its cause or intensity. To regulate such conflicts, a set of legal norms has been established under the 1949 Geneva Conventions and the 1977 Additional Protocol I, alongside customary international law, all of which emphasize the protection of those not participating in hostilities, such as civilians, prisoners of war, and the wounded. This thesis dedicates its first chapter to examining the personal scope of protection afforded to civilians during international armed conflicts, consisting of two main sections. The first addresses the concept of protection by analyzing the nature of international conflicts and legally defining who qualifies as a civilian under international law. The second section sets out the legal rules governing civilian protection, with particular attention to vulnerable groups, namely children and women, as stipulated in the Fourth Geneva Convention and Additional Protocol I. The second chapter focuses on the guarantees of effective civilian protection, with an emphasis on both preventive and punitive legal mechanisms. The first section analyzes preventive mechanisms, highlighting the role of states in acceding to international treaties and implementing them through legislative and educational measures, as well as the activation of international protection tools. The second section addresses deterrent mechanisms, including national and international judicial accountability processes for violators of international humanitarian law, thereby reinforcing the principle of non-impunity. This thesis presents an integrated perspective on the legal protection of civilians, balancing prevention and accountability through a comprehensive analysis of legal foundations, conceptual dimensions, and implementation mechanisms, with the aim of ensuring effective enforcement of international humanitarian law norms. ............................... الملخص تعد النزاعات المسلحة الدولية من أبرز التحديات التي تواجه المجتمع الدولي، لما تثيره من تعقيدات قانونية وسياسية وإنسانية. وقد عرّف القانون الدولي الإنساني النزاع المسلح الدولي بأنه الاشتباك القائم بين دولتين أو أكثر، دون النظر إلى أسبابه أو مستوى حدّته. ولتنظيم هذا النوع من النزاعات، أُقِرّت مجموعة من القواعد ضمن اتفاقيات جنيف لعام 1949 والبروتوكول الإضافي الأول لعام 1977، بالإضافة إلى الأعراف الدولية التي تؤكد على حماية غير المشاركين في القتال، مثل المدنيين، والأسرى، والجرحى. وفي هذه المذكرة، سنخُصّص الفصل الأول لدراسة النطاق الشخصي لحماية السكان المدنيين أثناء النزاعات المسلحة الدولية، وتضمن مبحثين رئيسيين. تناول المبحث الأول مفهوم الحماية من خلال تحليل طبيعة النزاعات الدولية وتحديد من يُعتبر مدنيًا بموجب القانون الدولي. أما المبحث الثاني سنعرض القواعد القانونية المقررة لحماية المدنيين، مع تركيز خاص على فئتي الأطفال والنساء، كما ورد في اتفاقية جنيف الرابعة والبروتوكول الإضافي الأول. بالنسبة للفصل الثاني، سندرس مسألة ضمان الحماية الفعلية للمدنيين من خلال التركيز على الآليات القانونية ذات الطابع الوقائي والردعي. حيث نركز في المبحث الأول الآليات الوقائية، من خلال إبراز دور الدول في الانضمام للاتفاقيات الدولية وتفعيلها تشريعيًا وتدريبيًا، إلى جانب تفعيل آليات الحماية الدولية. في حين نخُصص المبحث الثاني للآليات الردعية، التي تشمل الملاحقة القضائية وطنياً ودولياً لمحاسبة منتهكي قواعد القانون الدولي الإنساني، بما يكرّس مبدأ عدم الإفلات من العقاب. هذه المذكرة تقدم رؤية متكاملة للحماية القانونية للسكان المدنيين تجمع بين الوقاية والمساءلة، اعتمادا على الأسس القانونية والأبعاد المفاهيمية والآليات التطبيقية، بهدف ضمان تفعيل فعّال لقواعد القانون الدولي الإنساني. .............................. Résumé Les conflits armés internationaux comptent parmi les défis les plus importants auxquels la communauté internationale est confrontée, en raison des complexités juridiques, politiques et humanitaires qu'ils soulèvent. Le droit international humanitaire définit un conflit armé international comme un affrontement entre deux ou plusieurs États, quelles que soient ses causes ou son intensité. Pour encadrer ce type de conflit, un ensemble de règles a été établi dans les Conventions de Genève de 1949 et le Protocole additionnel I de 1977, en plus des normes internationales qui mettent l'accent sur la protection des non-combattants, tels que les civils, les prisonniers et les blessés. Dans ce mémorandum, nous consacrerons le premier chapitre à l'examen de la portée personnelle de la protection des civils lors des conflits armés internationaux. Il comprend deux sections principales. La première aborde le concept de protection en analysant la nature des conflits internationaux et en définissant qui est considéré comme un civil en droit international. La deuxième section présente les règles juridiques établies pour la protection des civils, en mettant l'accent sur les enfants et les femmes, telles que stipulées dans la Quatrième Convention de Genève et son Protocole additionnel I. Dans le deuxième chapitre, nous examinerons la question de la protection efficace des civils en nous concentrant sur les mécanismes juridiques à caractère préventif et dissuasif. La première section se concentre sur les mécanismes préventifs, soulignant le rôle des États dans l'adhésion aux accords internationaux et leur activation par la législation et la formation, ainsi que dans l'activation des mécanismes internationaux de protection. La deuxième section se concentre sur les mécanismes de dissuasion, notamment les poursuites nationales et internationales visant à traduire en justice les auteurs de violations du droit international humanitaire, consacrant ainsi le principe de non-impunité. Ce mémorandum présente une vision globale de la protection juridique des civils, alliant prévention et responsabilisation, fondée sur des fondements juridiques, des dimensions conceptuelles et des mécanismes de mise en œuvre, afin de garantir l'application effective du droit international humanitaire.
Keywords: Keywords: International Humanitarian Law; Civilians; Children; Women; International Armed Conflicts.; الكلمات المفتاحية: القانون الدولي الإنساني، المدنيين، الأطفال، النساء، النزاعات المسلحة الدولية.; Mots-clés : Droit international humanitaire; civils; enfants; femmes; conflits armés internationaux.